2020
DOI: 10.21037/qims-18-233
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of perfusion parameter in hypervascular hepatocellular carcinoma and focal nodular hyperplasia using dynamic susceptibility magnetic resonance imaging with super-paramagnetic iron oxide: comparison with single level dynamic CT arteriography

Abstract: Background: Dynamic susceptibility contrast MR imaging (DSC-MRI) offers direct evaluation of neovascularity. Ferucarbotran does not accumulate in the interstitial space, instead remaining in the intravascular space during early phase imaging. We investigate tracer kinetic analysis with DSC-MRI with ferucarbotran and single level CT during hepatic arteriography (SL-CTHA) in assessment of hypervascular hepatocellular lesions and evaluate the usefulness of DSC-MRI with ferucarbotran.Methods: Six patients having h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Approximately 90% of FNH and some HCA cases show hyperintensity in the HBP. The signal of FNH on T2WI imaging is close to that of normal liver parenchyma and often associated with a central scar (14). Intratumoral fat deposition and the atoll sign are typical features in HCAs but seldom observed in FNH (11).…”
Section: Populations (3)mentioning
confidence: 90%
“…Approximately 90% of FNH and some HCA cases show hyperintensity in the HBP. The signal of FNH on T2WI imaging is close to that of normal liver parenchyma and often associated with a central scar (14). Intratumoral fat deposition and the atoll sign are typical features in HCAs but seldom observed in FNH (11).…”
Section: Populations (3)mentioning
confidence: 90%
“…Pre-contrast MRI included T1-weighted images (in and opposed phase) and T2-weighted images. As previously reported, a total volume of 1.3-mL SPIO (36.2-mg Fe) was injected via the cubital vein at a rate of 3 mL per second, followed by 40-mL saline at the same speed ( 14 , 15 ). The scanning of perfusion study was started at 4 s after the beginning of SPIO injection, scanning took 50 s, and a hundred phases were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, the evaluation of tumor blood flow is a significant clue to decide the therapeutic strategy. We have previously evaluated the blood flow of HCC or hepatocellular nodules by SPIO and reported its effectiveness (13)(14)(15). On the other hand, the better or equal detection of the metastatic lesion with SPIO-enhanced MRI has been reported than with enhanced CT or enhanced MR using nonspecific extracellular contrast media (10,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…As a sensitive mean of detecting vascular changes, IONPs-enhanced SWI-MRI has been successfully translated to clinical research. 90 , 91 Some preclinical and clinical trials have indicated a close relationship between BV/VD and histologic results. 89 , 90 , 92 However, the morphological parameters of vessels may not reflect the real growth activity of tumor cells since the metabolic shift could compensate for the reduced vascular supply.…”
Section: Application Of Ionps In Guiding Tumor Therapy and Evaluating...mentioning
confidence: 99%